Factors Associated with Physical Work Stress among Photocopy Workers around Universitas Muhammadiyah Surakarta - Andika Fajar Dwi Saputra; Rezania Asyfiradayati (International Journal of Science and Environment (IJSE), 2026)
Physical work stress among photocopy workers is an important occupational health issue, often arising from prolonged working duration, years of service, and work fatigue. Preliminary observations identified common symptoms among workers, including headaches, eye strain, and back pain, indicating the presence of physical stress related to job demands. This study aimed to analyze the relationship between years of service, daily working duration, and work fatigue with physical work stress among photocopy workers around Universitas Muhammadiyah Surakarta. This study employed a quantitative analytic cross-sectional design with a total sampling technique involving 56 photocopy workers. Data were collected using a self-administered questionnaire, including the Industrial Fatigue Research Committee (IFRC) instrument to measure work fatigue and a modified NIOSH questionnaire to assess physical work stress, and analyzed using the Spearman rank correlation test. The results showed that years of service were not significantly associated with physical work stress (p = 0.539; r = -0.084). In contrast, daily working duration had a significant positive relationship with physical work stress (p = 0.001; r = 0.426), indicating a moderate correlation. The strongest relationship was found between work fatigue and physical work stress (p < 0.001; r = 0.823), demonstrating a very strong positive correlation. In conclusion, work fatigue is the most dominant factor associated with physical work stress among photocopy workers; therefore, interventions should prioritize fatigue management and the optimization of working duration.